Exploring the phenotype of Italian patients with ALS with intermediate ATXN2 polyQ repeats. Issue 11 (25th August 2022) - Chio, Adriano; Moglia, Cristina; Canosa, Antonio; Manera, Umberto; Grassano, Maurizio; Vasta, Rosario; Palumbo, Francesca; Gallone, Salvatore; Brunetti, Maura; Barberis, Marco; De Marchi, Fabiola; Dalgard, Clifton; et al.
Abstract : Objective: To detect the clinical characteristics of patients with amyotrophic lateral sclerosis (ALS) carrying an intermediate ATXN2 polyQ number of repeats in a large population-based series of Italian patients with ALS. Methods: The study population includes 1330 patients with ALS identified through the Piemonte and Valle d'Aosta Register for ALS, diagnosed between 2007 and 2019 and not carrying C9orf72, SOD1, TARDBP and FUS mutations. Controls were 1274 age, sex and geographically matched Italian subjects, identified through patients' general practitioners. Results: We found 42 cases and 4 controls with≥31 polyQ repeats, corresponding to an estimated OR of 10.4 (95% CI 3.3 to 29.0). Patients with≥31 polyQ repeats (ATXN2+) compared with those without repeat expansion (ATXN2−) had more frequently a spinal onset (p=0.05), a shorter diagnostic delay (p=0.004), a faster rate of ALSFRS-R progression (p=0.004) and King's progression (p=0.004), and comorbid frontotemporal dementia (7 (28.0%) vs 121 (13.4%), p=0.037). ATXN2+ patients had a 1-year shorter survival (ATXN2+ patients 1.82 years, 95% CI 1.08 to 2.51; ATXN2− 2.84 years, 95% CI 1.67 to 5.58, p=0.0001). ATXN2 polyQ intermediate repeats was independently related to a worse outcome in Cox multivariable analysis (p=0.006). Conclusions: In our population-based cohort, ATXN2+ patients with ALS have a distinctive phenotype, characterised by a more rapid disease course and a shorter survival. In addition, ATXN2+ patients have a more severe impairment of cognitive functions. These findings have relevant implications on clinical practice, including the possibility of refining the individual prognostic prediction and improving the design of ALS clinical trials, in particular as regards as those targeted explicitly to ATXN2 .